Dependence of the plastic rocks properties on the pressure change in the well - Mykhailovska, Olena; Soloviev, Veniamin (Academic journal Industrial Machine Building Civil Engineering, 2022)
Experimental studies of changes in rock properties depending on the pressure in the well and in the massif of the plastic layer at different distances from the well over time were carried out. The function demonstrates the power dependence of the pressure ratio at the moment of time on the geostatic pressure. After sealing the well, the pressure in the massif of the plastic formation increases in the near-well zone and decreases in the peripheral zone. Over time, the pressure in the massif of the plastic layer is equalized over the entire area of the layer. Pressure changes in a plastic rock have an impulse character. Thermal (residual) stresses affect the destruction of rocks during drilling with an increase in the depth of the well